Ultrasound-guided thoracic paravertebral injection in dogs: a cadaveric study. (May 2017) - Portela, Diego A.; Campoy, Luis; Otero, Pablo E.; Martin-Flores, Manuel; Gleed, Robin D.
Abstract: Objective: To describe ultrasound-visualized anatomy and the spread characteristics of a dye injected in the thoracic paravertebral (TPV) space under ultrasound guidance. Study design: Anatomic cadaver study. Animals: Seven dog cadavers. Methods: One cadaver was used to observe, identify, and describe the relevant TPV anatomy. In the remaining six, the left fifth TPV space was randomly assigned to be injected with either a low volume (LV; 0.05 mL kg −1 ) or high volume (HV; 0.15 mL kg −1 ) of dye. Subsequently, the contralateral side was injected with the alternative volume. Anatomic dissections were conducted to determine the incidence of complete spinal nerve staining (>1 cm circumferential coverage), number of contiguous spinal nerves dyed and the absence or presence of solution in particular locations. Results: The ultrasound-visualized anatomy of the TPV space was defined as the intercostal space abaxial to the vertebral body, delimited by the parietal pleura ventrally and the internal intercostal membrane dorsally. The endothoracic fascia divides the paravertebral space into dorsal and ventral compartments. The target nerve was completely dyed in five of six and six of six injections in the LV and HV conditions, respectively. In one LV injection, the nerve was partially dyed. No multisegmental spread affecting contiguous spinal nerves was found in either treatment. Multisegmental spread was found in the ventral compartment of the TPV space, affecting the sympathetic trunk on 3 (0–3) and 3.5 (1–6) vertebral spinal levels in the LV and HV conditions, respectively, but differences between volumes were not significant. No intrapleural, ventral mediastinal or epidural migration was observed. Conclusions and clinical relevance: Ultrasound-guided TPV block is a potentially reliable technique. The LV appeared sufficient to dye a single spinal nerve and multiple sympathetic trunk vertebral levels. Multiple TPV injections may be needed to provide adequate thoracic analgesia in dogs undergoing thoracic surgery.